A Simple System for Differentiation of Functional Intestinal Stem Cell-like Cells from Bone Marrow Mesenchymal Stem Cells - Lei Ye; Lei X. Sun; Min H. Wu; Jin Wang; Xin Ding; Hui Shi; Sheng L. Lu; Lin Wu; Juan Wei; Liang Li; Yu F. Wang (Elsevier, 2018)
Disruption of normal barrier function is a fundamental factor in the pathogenesis of inflammatory bowel disease, and intestinal stem cell (ISC) transplantation may be an optional treatment for patients. However, it is complicated and inefficient to isolate ISCs from the intestine, which hampers its wide application in clinic. We developed a two-step protocol in which mesenchymal stem cells (MSCs) were first induced into Sox17- or Foxa2-positive definitive endoderm cells by activin A treatment and then into Lgr5-positive ISC-like cells by miR-17 and FGF2 treatment. Furthermore, these Lgr5-positive cells could differentiate into enterocyte-like cells following induction with EGF. The results from an in vivo experiment showed that the MSC-derived Lgr5-positive cells were able to protect against dextran sulfate sodium-induced colitis. Taken together, our work might provide a new source of autologous ISCs. Keywords: mesenchymal stem cells, differentiation, intestinal stem cells